Practicing mind‐body medicine before Freud: John G. Gehring, the "Wizard of the Androscoggin". Issue 2 (14th October 2019) - Harris, Ben; Stevens, Courtney J.
Abstract: This article describes the psychotherapy practice of physician John G. Gehring and places it in historical context. Forgotten today, Gehring was a highly sought‐after therapist from the 1890s to the 1920s by prominent figures in the arts, sciences, business, and law. He practiced a combination of work therapy, suggestion, and autosuggestion that has similarities to Cognitive Behavior Therapy and Behavioral Activation. Using biographies, memoirs, and archival records, the details of Gehring's work are reconstructed and the reasons for its success are analyzed. His invisibility in the history of psychiatry is attributed to the later dominance of Freudianism within the field.